Relationship between pregnant women's combined exposure to heavy metals and their offspring's congenital heart defects in Lanzhou, China - Chen, Lulu; Zhao, Yaqin; Sun, Jianhao; Jiao, Xinjuan; Wu, Zhenzhen; Wang, Jian; Qiu, Jie; Mao, Baohong; Liu, Qing (Frontiers in Pediatrics, 2025)
Abstract Background: Previous research has demonstrated that exposure to individual heavy metals elevates the incidence rate of congenital heart defects (CHDs). However, there is a paucity of data concerning the relationship between combined exposure to multiple heavy metals and the occurrence of CHDs. This study seeks to investigate the association between combined heavy metal exposure in pregnant women and the incidence of CHDs in their offspring in Lanzhou, China. Methods: We conducted a comprehensive review of the birth cohort study undertaken at our hospital from 2010 to 2012, with the objective of investigating the association between combined heavy metal exposure in pregnant women and the incidence of CHDs in their offspring. This analysis was performed utilizing a multifactorial conditional logistic regression model. Result: A nested case-control study was conducted involving 97 case groups and 194 control groups. The research identified a significant correlation between the concentrations of nickel (Ni), lead (Pb), and titanium (Ti) in the blood of pregnant women and the risk of CHDs. Specifically, compared to low exposure levels, elevated concentrations of Ni in maternal blood were associated with a 2.098-fold increase in the risk of CHDs in offspring (OR 3.098, 95% CI 1.322-7.260). Similarly, high levels of Pb in maternal blood were linked to a 1.192-fold increase in the risk of CHDs in offspring (OR 2.192, 95% CI 1.021-4.707). Furthermore, elevated levels of Ti in maternal blood were also associated with an increased risk of CHDs. Elevated Ti exposure levels in maternal blood are associated with a 3.065-fold increased risk of CHDs in offspring (OR 4.065, 95% CI 1.887-8.758). When compared to low exposure levels, the combined exposure to four heavy metals in the blood of pregnant women is linked to a 4.946-fold increased risk of CHDs in their offspring (OR 5.946, 95% CI 2.872-12.309). Conclusion: The cumulative exposure levels of Ni, barium (Ba), Pb, and Ti in the blood of pregnant women are correlated with an elevated risk of CHDs in their offspring.